Livelihood choices and returns among pastoralists: Evidence from southern Kenya - Radeny, Maren A.O.; Nkedianye, D.; Kristjanson, Patricia M.; Herrero, Mario (Berghahn Books, 2007)
This article uses qualitative and quantitative data to document the nature of educational practices in a pastoralist area in Tanzania, and to provide evidence that the schooling process, amongst other influences, has encouraged and facilitated the uptake and expansion of farming by these pastoralists. The article argues that the schooling process has influenced pastoralists’ livelihood choices, and thus the nature and viability of pastoralism.